The axiomatic definitions of some group decision rules - Morkeliūnas, A. (Lithuanian Mathematical Journal, 1971)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: А. И. Моркелюнас. Аксиоматическое определение некоторых групповых решений A. Morkeliūnas. Kai kurių grupinių sprendimų aksiomatiniai apibrėžimai